Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berfikir Kritis Dan Pemecahan Masalah Pada Fase D Materi Struktur Dan Fungsi Tumbuhan: (The Effect of The Problem Based Learning Model on Critical Thinking and Problem Solving Abilities in Phase D of Plant Structure And Function Material) - Juniandra, Rezha; Hamidah, Afreni; Anggreini , Evita (BIODIK, 2025)
Education in the 21st century demands the development of essential skills such as critical thinking and problem solving, which are known as part of the 4C skills. However, initial observations at SMP 7 Muaro Jambi showed that these two skills were not optimal among students. This can be seen from the lack of active involvement of students in discussions and problem solving in class. The results of the questionnaire distributed to 64 students reinforced this finding, showing a low percentage in various aspects of critical thinking (for example, only 45% of students were able to ask questions and analyze arguments, and 46% in providing conclusions) and problem solving (only 40% of students were able to solve problems effectively). In addition, interviews with science teachers revealed how difficult it is for students to understand abstract material such as the structure and function of plants, which should be related to everyday life but are still presented theoretically without space for critical discussion. This condition has a negative impact on student development, making them tend to memorize without deep understanding and have difficulty applying knowledge in new situations. To overcome this problem, this study aims to examine the effect of the Problem Based Learning (PBL) learning model in improving students' critical thinking and problem-solving skills on the material of plant structure and function. PBL was chosen because this model focuses on students, encourages discussion, exploration, and independent problem solving, which are very relevant to developing both abilities. Various previous studies have also proven the effectiveness of PBL in facilitating learning of complex materials and increasing student engagement. Pendidikan di abad ke-21 menuntut pengembangan kemampuan esensial seperti berpikir kritis dan pemecahan masalah, yang dikenal sebagai bagian dari keterampilan 4C. Namun, observasi awal di SMP 7 Muaro Jambi menunjukkan bahwa kedua kemampuan ini belum optimal di kalangan peserta didik. Hal ini terlihat dari kurangnya keterlibatan aktif siswa dalam diskusi dan pemecahan masalah di kelas. Hasil angket yang disebarkan kepada 64 siswa memperkuat temuan ini, menunjukkan persentase yang rendah pada berbagai aspek berpikir kritis (misalnya, hanya 45% siswa mampu memberikan pertanyaan dan menganalisis argumen, serta 46% dalam memberikan kesimpulan) dan pemecahan masalah (hanya 40% siswa yang mampu memecahkan masalah secara efektif). Selain itu, wawancara dengan guru mata pelajaran IPA mengungkapkan adanya kesulitan siswa dalam memahami materi abstrak seperti struktur dan fungsi tumbuhan, yang seharusnya dapat dikaitkan dengan kehidupan sehari-hari namun masih disampaikan secara teoritis tanpa ruang diskusi kritis. Kondisi ini berdampak negatif pada perkembangan siswa, membuat mereka cenderung menghafal tanpa pemahaman mendalam dan kesulitan menerapkan pengetahuan dalam situasi baru. Untuk mengatasi permasalahan ini, penelitian ini bertujuan untuk mengkaji pengaruh model pembelajaran Problem Based Learning (PBL) dalam meningkatkan kemampuan berpikir kritis dan pemecahan masalah siswa pada materi struktur dan fungsi tumbuhan. PBL dipilih karena model ini berpusat pada siswa, mendorong diskusi aktif, eksplorasi, dan pemecahan masalah secara mandiri, yang sangat relevan untuk mengembangkan kedua kemampuan tersebut. Berbagai penelitian sebelumnya juga telah membuktikan efektivitas PBL dalam memfasilitasi pembelajaran materi kompleks dan meningkatkan keterlibatan siswa.